Saddam versus the inspectors: the impact of regime security on the verification of Iraq's WMD disarmament. Issue 3 (16th April 2018) - Koblentz, Gregory D.
ABSTRACT: The discovery that Iraq had no weapons of mass destruction (WMD) in 2003 raised the question of why Saddam had prevented UN weapons inspectors from fully accounting for his disarmament. The leading explanation for Saddam's behavior is that he valued ambiguity as part of a strategy of 'deterrence by doubt'. This article argues that Iraq's obstruction of inspectors in the late 1990s was motivated by his desire to shield Iraq's regime security apparatus from UNSCOM's intrusive counter-concealment inspections. The failure to understand how strongly Saddam's concerns about his personal safety drove Iraq's contentious relationship with UNSCOM set the stage for the invasion of Iraq in 2003.